Analysis Qualitative Administrative Medical Records Documents Of Inpatients With Typhoid In Regional Hospital Dr. Soebandi Jember 2018 - Angga Ferdianto (NHM PRESS, 1970)
Analysis Qualitative Administrative of medical record documents are indispensable for the creation of the content of health records which are protected from inputs that are not erect/consistent as well as violation of the recordings that have an impact on the inaccurate and incomplete results. The purpose of this research was to determine completeness of the description of contents medical records document of hospitalization in patients with Typhoid in RSD dr. Soebandi Jember Year 2018. The type of this research was qualitative descriptive research. Data acquisition of this research were observation. Results obtained from medical record document observation in RSD dr. Soebandi Jember, incomplete filling of informed consent are as many as 34 files. Assessing the recording as much as 6 files on aspects of writing unreadable no writing illegible physician.